Nutritional rickets at puberty - Moncrieff, M. W. (1973)
Four adolescent Asians with vitamin D deficiency rickets were seen in Derby in the 5 years 1967 to 1971. They had an extremely low intake of vitamin D, and this, combined with the extra metabolic demands of puberty, was judged to be the main cause of the rickets. However, since investigation of their sibs revealed 4 further cases of rickets, it is possible that some of these children had an inherited disability in the metabolism of vitamin D. 2 cases of iron deficiency anaemia were found among their sibs. We suspect that nutritional deficiencies may be widespread in the Asian community in Britain and that prevention depends on dietary education.